Carcinogenic and non-carcinogenic risk assessment of exposure to trace elements in groundwater resources of Sari city, Iran. (15th March 2023) - Niknejad, Hadi; Ala, Alireza; Ahmadi, Fatemeh; Mahmoodi, Hamed; Saeedi, Reza; Gholami-Borujeni, Fathollah; Abtahi, Mehrnoosh
Abstract: The daily intake of trace elements through water resources and their adverse health effects is a critical issue. The purpose of this research was to assess the carcinogenic and non-carcinogenic risks of exposure to iron (Fe), copper (Cu), manganese (Mn), zinc (Zn), chromium (Cr), lead (Pb), and arsenic (As) in groundwater resources of Sari city, Iran. The concentrations of the trace elements in a total number of 66 samples from the groundwater sources were measured using inductively coupled plasma mass spectrometry (ICP-MS). The hazard index (HI) levels of exposure to the trace elements from the groundwater sources for adults, teenagers, and children were 0.65, 0.83, and 1.08, respectively. The carcinogenic risk values of Cr and As in the groundwater sources for children, teenagers, and adults were 0.0001, 0.00009, 0.00007, 0.0003, 0.0002, and 0.0001, respectively, causing a total carcinogenic risk value higher than the acceptable range, and removing Cr and As from the groundwater resources is recommended for safe community water supply. HIGHLIGHTS: The most important goals of the current research are to (1) determine the concentration of heavy metals in the drinking water and (2) assess the carcinogenic and non-carcinogenic risks of heavy metals through water ingestion by adults, teenagers, and children in the study areas. Total carcinogenic risk value of the heavy metals in drinking water was higher than the acceptable range. Graphical Abstract